2015
DOI: 10.1002/cbf.3132
|View full text |Cite
|
Sign up to set email alerts
|

ODAM inhibits RhoA‐dependent invasion in breast cancer

Abstract: Odontogenic ameloblast-associated protein (ODAM) contributes to cell adhesion. In human cancer, ODAM is down-regulated, and the overexpression of ODAM results in a favourable prognosis; however, the molecular mechanisms underlying ODAM-mediated inhibition of cancer invasion and metastasis remain unclear. Here, we identify a critical role for ODAM in inducing cancer cell adhesion. ODAM induced RhoA activity and the expression of downstream factors, including Rho-associated kinase (ROCK). ODAM-mediated RhoA sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…These results also confirm the accuracy of our results. For other genes that are not included in the Sanger database, we also confirm their important role in cancer-related biological processes through literature verification, such as ETS1 (Watabe et al, 1998;Fujimoto et al, 2004;Zhang et al, 2014;Li et al, 2015) and RHOA (Lee et al, 2015;Zeng et al, 2015;Sun et al, 2016) in hallmark "Activating Invasion and Metastasis".…”
Section: Validation Of Chg Datamentioning
confidence: 55%
“…These results also confirm the accuracy of our results. For other genes that are not included in the Sanger database, we also confirm their important role in cancer-related biological processes through literature verification, such as ETS1 (Watabe et al, 1998;Fujimoto et al, 2004;Zhang et al, 2014;Li et al, 2015) and RHOA (Lee et al, 2015;Zeng et al, 2015;Sun et al, 2016) in hallmark "Activating Invasion and Metastasis".…”
Section: Validation Of Chg Datamentioning
confidence: 55%
“…It was reported that ODAM expression induced PTEN expression and inactivated the PI3K/AKT pathway in melanoma 47 and CRC cells 42 . Another group reported that ODAM suppressed migration and invasion through an increase in RhoA expression in breast cancer cells 48 . These reports suggested the tumor‐suppressive role of ODAM in human carcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“… 42 Another group reported that ODAM suppressed migration and invasion through an increase in RhoA expression in breast cancer cells. 48 These reports suggested the tumor‐suppressive role of ODAM in human carcinogenesis. However, this view raised a discrepancy between its growth‐suppressive role and its elevated expression in cancer because cancer cells expressing abundant ODAM should not be selected in tumor evolution.…”
Section: Discussionmentioning
confidence: 99%
“…RHOA is the target of miR-146a to prevent cell invasion and metastasis in breast cancer (Liu et al, 2016). Lee et al showed that ODAM expression maintains breast cancer cell adhesion and thus prevents breast cancer cell metastasis by modulating RhoA signaling in breast cancer cells (Lee et al, 2015). The study by Kwon et al showed that SMURF1 acts in EGF-induced migration and invasion of breast cancer cells (Kwon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%